Reduction of reactive oxygen species production and membrane damage during storage of 'Daw' longan fruit by chlorine dioxide - Warunee Chomkitichai (2018)
The effects of gaseous chlorine dioxide (ClO2) fumigation on reactive oxygen species (ROS) levels and membrane damage during storage of harvested 'Daw' longan fruit were evaluated. Fresh longan fruits were collected and separated into two groups; the non-treated (control) group and the fumigated group, which were treated with 10mg/L ClO2for 10min. The fruits were then packed into cardboard boxes and stored at 25±1°C at RH 82±5% for 7 days. ROS levels, including superoxide radical (O2-), hydrogen peroxide (H2O2) and hydroxyl radical (OH) increased during storage. In addition, membrane damage, as measured by electrolyte leakage (EL) rate, lipoxygenase (LOX) activity and conjugated diene and malondialdehyde (MDA) contents also increased. These increases coincided with the onset of pericarp browning. ClO2fumigation reduced ROS production and membrane damage during storage. Levels of O2-, H2O2and OH, EL rate, LOX activity, conjugated diene and MDA contents were all significantly lower in the fumigated group than those in the control group and were correlated with browning index. ROS increased with increasing membrane damage and browning. ClO2fumigation reduced the production of free radicals which cause membrane damage and may therefore be an effective treatment to alleviate longan browning during storage. © 2014 Elsevier B.V.